Assessing the environmental effects related to quantum dot structure, function, synthesis and exposure. Issue 3 (6th December 2021) - Giroux, Marissa S.; Zahra, Zahra; Salawu, Omobayo A.; Burgess, Robert M.; Ho, Kay T.; Adeleye, Adeyemi S.
Abstract : Quantum dots (QDs) have unique properties, which make them valuable in some commercial technologies. This review discusses the major types and applications of QDs, their potential environmental exposures, fates, and adverse effects on organisms. Abstract : Quantum dots (QDs) are engineered semiconductor nanocrystals with unique fluorescent, quantum confinement, and quantum yield properties, making them valuable in a range of commercial and consumer imaging, display, and lighting technologies. Production and usage of QDs are increasing, which increases the probability of these nanoparticles entering the environment at various phases of their life cycle. This review discusses the major types and applications of QDs, their potential environmental exposures, fates, and adverse effects on organisms. For most applications, release to the environment is mainly expected to occur during QD synthesis and end-product manufacturing since encapsulation of QDs in devices prevents release during normal use or landfilling. In natural waters, the fate of QDs is controlled by water chemistry, light intensity, and the physicochemical properties of QDs. Research on the adverse effects of QDs primarily focuses on sublethal endpoints rather than acute toxicity, and the differences in toxicity between pristine and weathered nanoparticles are highlighted. A proposed oxidative stress adverse outcome pathway framework demonstrates the similarities among metallic and carbon-based QDs that induce reactive oxygen species formation leading to DNA damage, reduced growth, and impaired reproduction in several organisms. To accurately evaluate environmental risk, this review identifies critical data gaps in QD exposure and ecological effects, and provides recommendations for future research. Future QD regulation should emphasize exposure and sublethal effects of metal ions released as the nanoparticles weather under environmental conditions. To date, human exposure to QDs from the environment and resulting adverse effects has not been reported.